PENGARUH LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN STIE NASIONAL BANJARMASIN - Ferli Erwansyah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This research aimed to give empirical evidences about the effect of work environtment to work passion of employee in STIE Nasional Banjarmasin. The variables in this study were work environtment and work passion.The population in this study was the employee in STIE Nasional Banjarmasin. The data collected from the output of questionnaires which gived to the respondents. The samples technique used total sampling with 50 samples.The research gived empirical evidences that there were positive effect of work envirenment to work passion of employee in STIE Nasional Banjarmasin.